Dissemination of Micro and Small Business Licensing to Increase Awareness of the Importance of Business Licensing - Latifah, Luluk Latifah; Nasrullah, Dede; Huda, Fatkur (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2024)
The low level of ownership of business legality is caused by the lack of knowledge of MSE actors regarding the benefits and importance of ownership of business licenses as well as limited information regarding procedures for managing business legality. To overcome the above problems, it is necessary to support and assist the development of UMK in Bulak village. This community service activity aims to increase the knowledge, awareness and skills of stakeholders in Bulak Village on the importance of the Business Identification Number (NIB) for MSEs in increasing the economic resilience of the region. Service activities are carried out through focus group discussion, counseling and question and answer methods. The results obtained in this study indicate that many MSEs do not have business legality, because they do not understand the importance of a business license and how to manage it. So it takes escort by the closest stakeholders or the relevant government in providing information about the benefits of having a business license (NIB), why you have to have an NIB, how to get an NIB, and motivating stakeholders to encourage MSEs to get business permits.